Relationship Between Lipodystrophy, Body Composition, Metabolic Profile, and Serum Levels of Adipocytokines - Sacilotto, Lívia Bertazzo; Papini, Silvia Justina; Mendes, Adriana Lucia; Gatto, Mariana; Pereira, Paulo Câmara Marques; Corrente, José Eduardo; Silva, Julhiany de Fátima da (Frontiers in Nutrition, 2021)
Due to the decrease in the opportunistic infections’ frequency, we observed a transition of nutritional status of people living with HIV/aids (PLWHA), previously characterized by intense weight loss and malnutrition (or "Wasting Syndrome"); by excessive weight gain, which makes them overweight or obese individuals, even after antiretroviral therapy (ART). Despite the benefits at clinical state improvement of PLHA, some side effects associated with the use of ART are reported. The redistribution of body fat has been associated with the treatment and is characterized by morphological changes, also known as lipodystrophy. The complications of metabolic and morphological changes in these individuals carry aesthetic consequences, in addition to increasing the risk of cardiovascular and pancreatic diseases development. Thereby, it is oriented that the nutritional assessment is accurate not only to measure the change in total body weight, but to quantify and locate the distribution of fat accumulation as well. The adipocytokines are proteins with essential functions to biological processes, wherein these proteins’ levels are related to the pathogenesis of the metabolic syndrome and cardiovascular disease. Recent studies have shown that such levels are usually modified in people living with HIV/aids, regardless of whether the treatment is established or not. An application of methods for body fat estimation on patients with fat redistribution, as in the case of aids, especially those that quantify body fat by segments. This is an important indicator of nutritional assessment in order to define, in clinical practice, the most appropriate treatment for the prevention of comorbidities.